2018
DOI: 10.4236/ojpsych.2018.81002
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship among Chronic Disease, Feeling-for-Their-Age, Sleep Quality, Health-Related Quality of Life and Activities of Daily Living of Community-Dwelling Persons over 55 Years of Age

Abstract: Japan's aging population rate is increasing and healthy life expectancy has decreases by 10 years shorter than average life expectancy. The aim of this study is to determine the relationship among chronic disease, sleep quality, health-related quality of life (HRQOL), and activities of daily living in people over 55 years old who live in the community. Subjects were 161 persons aged 57 to 90 years who were treated with chronic disease in the outpatient department of the A hospital. Exclusion criteria included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…The literature on this subject reveals contradictory data, as certain studies highlight the high burden of care and dependency necessary for these types of patients (Forjaz et al., 2015; Hudon et al., 2015) compared to other research, such as ours, which found a moderate dependency and a greater patient autonomy (Mokraoui et al., 2016). Nonetheless, there is certain agreement regarding the areas where the quality of life of these patients is most affected, highlighting mobility issues (moderate and severe problems in almost half of patients) and the presence of pain (Sugimoto et al, 2018). It seems reasonable to believe that musculoskeletal problems are highly prevalence and, together with pain, these appear as major disabling factors (Steingrímsdóttir et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The literature on this subject reveals contradictory data, as certain studies highlight the high burden of care and dependency necessary for these types of patients (Forjaz et al., 2015; Hudon et al., 2015) compared to other research, such as ours, which found a moderate dependency and a greater patient autonomy (Mokraoui et al., 2016). Nonetheless, there is certain agreement regarding the areas where the quality of life of these patients is most affected, highlighting mobility issues (moderate and severe problems in almost half of patients) and the presence of pain (Sugimoto et al, 2018). It seems reasonable to believe that musculoskeletal problems are highly prevalence and, together with pain, these appear as major disabling factors (Steingrímsdóttir et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This case description presentation is part of a larger study, in which an initial sample of 161 patients in the outpatient department, age 55 years and older who were being treated at Hospital "A" for various chronic ailments [2], were screened. Of these, 66 participants were selected, those who had PSQI-J (Japanese version Pittsburgh Sleep Quality Index) scores of less than six [14,15].…”
Section: Case Description/presentationmentioning
confidence: 99%
“…A previous study [2] described the influence of chronic disease, sleep quality, health-related quality of life (HRQOL) and daily living activities of community-dwelling persons over 55 years of age on living fulfilling lives. The findings showed that good sleep quality was related to the participants' feeling-for-theirage, in that, because they felt younger physically, they were able to sleep better.…”
Section: Introductionmentioning
confidence: 99%